Perdebatan dalam Al-Qur’an: Analisis Tematik Ayat-Ayat Mujadalah yang Turun di Makkah (Makkiyyah) - Zulfan Nabrisah (Islamika Inside: Jurnal Keislaman dan Humaniora, 2020)
Abstract: This study discusses the dispute between the infidels and prophets mentioned in the Qur’an (mujadalah verses). Therefore, the study used refers to the maudu’i method (thematic method). The study concludes that the topic of the mujadalah verses consists of (1) the dispute is a natural human tendency (fiṭrah); (2) the prophets and the truth of the divine revelation were always disputed by the infidel (kāfir); (3) Allah commands the believers (mu’mīn) to debate them wisely (ḥasanah), even though the infidels use the despicable manner (baṭil), and; (4) Allah will difinitely punishes anyone who denies the truth of His revelation.